Heparin-Induced Thrombocytopenia in a Patient with Essential Thrombocythemia: A Case Based Update - Edva Noel; Naeem Abbas; Yevegeniy Skaradinskiy; Zwi Schreiber (Case Reports in Hematology)
Vascular thrombosis is a common clinical feature of both essential thrombocythemia (ET) and heparin-induced thrombocytopenia (HIT). The development of HIT in a patient with ET is rare and underrecognized. We report the case of a 77-year-old woman with preexisting ET, who was admitted with acute coronary syndrome, and IV heparin was started. She was exposed to unfractionated heparin (UFH) 5 days prior to this admission. Decrease in platelet count was noted, and HIT panel was sent. Heparin was discontinued. Patient developed atrial fibrillation, and Dabigatran was started. On day three, patient also developed multiple tiny cerebral infarctions and acute right popliteal DVT. On day ten of admission, HIT panel was positive, and Dabigatran was changed to Lepirudin. Two days later, Lepirudin was also discontinued because patient developed pseudoaneurysm on the right common femoral artery at the site of cardiac catheterization access. A progressive increase in the platelet count was noted after discontinuing heparin. Physicians should be aware of the coexistence of HIT and ET, accompanied challenges of the prompt diagnosis, and initiation of appropriate treatment.